2019
DOI: 10.1523/jneurosci.2070-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Translocator Protein Ligand Protects against Neurodegeneration in the MPTP Mouse Model of Parkinsonism

Abstract: Parkinson's disease is the second most common neurodegenerative disease, after Alzheimer's disease. Parkinson's disease is a movement disorder with characteristic motor features that arise due to the loss of dopaminergic neurons from the substantia nigra. Although symptomatic treatment by the dopamine precursor levodopa and dopamine agonists can improve motor symptoms, no diseasemodifying therapy exists yet. Here, we show that Emapunil (AC-5216, XBD-173), a synthetic ligand of the translocator protein 18, amel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 104 publications
5
39
0
Order By: Relevance
“…18 Reduction of neurons in SNc which project to CPu reflects the nigrostriatal system neurodegeneration after MPTP treatment, suggesting the mouse model of PD was successful ( Figure 5B and D). Consistent with the previous studies, 15 after five days of MPTP injection, a 56% loss of dopaminergic cell bodies in the SNc was observed. 22 The reduction in the number of retrogradely labelled SNc neurons further confirmed MPTP-induced neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
“…18 Reduction of neurons in SNc which project to CPu reflects the nigrostriatal system neurodegeneration after MPTP treatment, suggesting the mouse model of PD was successful ( Figure 5B and D). Consistent with the previous studies, 15 after five days of MPTP injection, a 56% loss of dopaminergic cell bodies in the SNc was observed. 22 The reduction in the number of retrogradely labelled SNc neurons further confirmed MPTP-induced neurodegeneration.…”
Section: Discussionsupporting
confidence: 92%
“…These findings were accompanied by prevention of retinal degeneration after injury, hence drastically inhibiting the progression of disease [109]. XBD173 has also been shown to decrease pro-inflammatory cytokines and delay Multiple Sclerosis progression and symptoms in an experimental autoimmune encephalomyelitis (EAE) mouse model [110], and also demonstrated efficacy in attenuating microglial activation and neuronal loss in an MPTP Parkinson's disease model [111].…”
Section: In Vivo Immunomodulation Of Tspo Ligandsmentioning
confidence: 99%
“…Previously mentioned evidence about the protective activity of TSPO ligands in CNS disorders has initiated investigations about their effects concerning neurodegeneration. On this account, a study by Gong et al showed that Emapunil, a novel synthetic TSPO ligand, significantly reduced dopaminergic loss in mice with induced PD by inhibiting the unfolded protein response and subsequently reducing cellular stress and apoptosis [65]. Additionally, the authors concluded that the neuroprotective effect of Emapunil might be associated with the partial alteration of neurosteroid levels, which can counteract neuroinflammatory responses [65].…”
Section: Tspo and Parkinson Disease (Pd)mentioning
confidence: 99%
“…On this account, a study by Gong et al showed that Emapunil, a novel synthetic TSPO ligand, significantly reduced dopaminergic loss in mice with induced PD by inhibiting the unfolded protein response and subsequently reducing cellular stress and apoptosis [65]. Additionally, the authors concluded that the neuroprotective effect of Emapunil might be associated with the partial alteration of neurosteroid levels, which can counteract neuroinflammatory responses [65]. Together with other studies applying TSPO ligands for the treatment of brain damage, this investigation showed promising results about exploiting TSPO as a possible therapeutic target for α-synucleinopathies [28,66].…”
Section: Tspo and Parkinson Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation